Application of electrical sensor in total knee arthroplasty training - JIANG Ling, LIU Yan-qing, TIAN Hua (Jichu yixue yu linchuang, 2020)
Objective Soft tissue balancing in knee joint is a key technique for successful operation of total knee arthroplasty(TKA). There is not a widely accepted metric for balance, manual balance has been achieved primarily through tactile feedback and visual cue. That makes difficulties in learners'training. A new electronic sensor can measure the pressure of medial and lateral compartment of knee, and is applied in the skill training of total knee arthroplasty. Methods Five trainee surgeons attended 14 electronic sensor balancing TKA separately, there are 70 cases in total. Trainee surgeons did manual balance, then it was checked by electronic sensor in 0°,45°,90°knee position. All cases were divided into 7 groups according to chronological order. The unbalance cases were recorded in each group and compared statistically. Results For 0°,45°,90°knee position, the first group has 7,6,5 unbalance cases respectively. During the training, the unbalance case number is decreasing, the seventh group has 1,1,2 unbalance cases at last. There is significant difference between the first and the seventh group for 0°,45°. It is demanding for 45°balancing with most unbalance cases. Conclusions Electronic sensor is a new tool for TKA training. It helps the trainee surgeons to master soft tissue balancing technique quickly and effectively.